Zooplankton resting egg banks in permanent and temporary tropical aquatic systems - Araújo,Luciana Rabelo (2013)
AIM: We evaluated zooplankton resting egg banks and active communities in five coastal lagoons and in five temporary pools, aiming to compare the active and the dormant communities in such environments. As they differ in hydroperiod, we expected that pools present richer resting egg banks in comparison to those found in lagoons. METHODS: Zooplankton community was sampled twice in 2006 (lagoons) and in 2010 (pools) and resting egg banks were sampled once in December 2007 (lagoons) and in May 2010 (pools). Resting eggs were isolated from the sediment by applying the sugar flotation method. RESULTS: In opposition to our expectation, species richness in the resting egg banks of pools did not differ from those of lagoons. Additionally, no difference was found between the active and the dormant zooplankton communities in each water body for both temporary and permanent environments. However, similarity between active and dormant communities was greater in permanent environments than it was in temporary environments. CONCLUSIONS: It seems that the diapause strategy observed in certain tropical zooplankton populations cannot be predicted based on the awareness of the environment type (permanent or temporary), since hatching cues may be species-specific.